The Role of Political Parties in Parliamentary Systems: Iraqi Parties Case Study (Journal of Social Sciences Review, 2025)
This research seeks to determine the effect of political parties on parliamentary systems in Iraq; parties play a key role in influencing and shaping decision-making, focusing on the Iraqi situation as a model. The research reviews the challenges facing Iraqi parties, such as the sectarian and ethnic division, which led to their weak ability to interact positively with society. It also indicates that many parties lack clear and effective programs, which negatively affects their ability to achieve the desired change. Parties play a pivotal role in the formation of governments, and corruption and exclusionary practices have a negative impact on the democratic process. At the end of the study, suggestions are made for how to make political parties work better. These include building a stronger sense of national identity and making programs that cover everyone's needs. This will help make the Iraqi parliamentary system more stable and effective.
Keywords: Parliamentary Systems; Political Parties; Political Pluralism; Elections; Political System